Lack of the pattern recognition molecule mannose-binding lectin increases susceptibility to influenza A virus infection - Hartshorn Kevan L; Thiel Steffen; McClear Sheree; Moyo Patience; White Mitchell R; Chang Wei-Chuan; Takahashi Kazue (BMC Immunology, 2010)
Abstract Background Mannose-binding lectin (MBL), a pattern recognition innate immune molecule, inhibits influenza A virus infection in vitro. MBL deficiency due to gene polymorphism in humans has been associated with infection susceptibility. These clinical observations were confirmed by animal model studies, in which mice genetically lacking MBL were susceptible to certain pathogens, including herpes simplex virus 2. Results We demonstrate that MBL is present in the lung of naïve healthy wild type (WT) mice and that MBL null mice are more susceptible to IAV infection. Administration of recombinant human MBL (rhMBL) reverses the infection phenotype, confirming that the infection susceptibility is MBL-mediated. The anti-viral mechanisms of MBL include activation of the lectin complement pathway and coagulation, requiring serum factors. White blood cells (WBCs) in the lung increase in WT mice compared with MBL null mice on day 1 post-infection. In contrast, apoptotic macrophages (MΦs) are two-fold higher in the lung of MBL null mice compared with WT mice. Furthermore, MBL deficient macrophages appear to be susceptible to apoptosis in vitro. Lastly, soluble factors, which are associated with lung injury, are increased in the lungs of MBL null mice during IAV infection. These results suggest that MBL plays a key role against IAV infection. Conclusion MBL plays a key role in clearing IAV and maintaining lung homeostasis. In addition, our findings also suggest that MBL deficiency maybe a risk factor in IAV infection and MBL may be a useful adjunctive therapy for IAV infection.